Deteksi Dini dan Pencegahan Risiko Bunuh Diri pada Remaja: Tinjauan Pustaka - wenly susanto (Cermin Dunia Kedokteran, 2025)
Suicide cases in adolescents are a concern to the World Health Organization (WHO) for immediate early detection, prevention, and management. Medical personnel should be more aware of risk factors, signs, and symptoms, and provide solutions. There are internal and external factors that underlie suicidal behavior. The level of suicidal behavior varies from person to person, early detection is needed. Early detection can be done by using screening tools that assess suicidal thoughts and attempts. The important role of the family as the first place to grow is also very much needed. The family will be a support system in the prevention of suicidal behavior. Cross-sectoral collaboration was needed to reduce the incidence of suicide in adolescents. Health workers need to have comprehensive knowledge and understanding of suicidal behavior. Suicidal behavior disorders need to be identified immediately to determine interventions that are appropriate to the patient’s condition. pharmacological and pharmacological therapies are needed to prevent suicidal behavior. Follow-up after therapy needs to be considered in terms of preventing recurrent suicidal behavior.